TOOLS FOR INCREASING EFFICIENCY IN DISTANCE LEARNING - Ibodullayeva Zubayda Sherzodovna (The latest pedagogical and psychological innovations in education, 2025)
This article investigates various tools and technologies that enhance the efficiency of distance learning. With the rapid shift to online education, selecting the right digital platforms and instructional tools has become essential for maintaining learner engagement and academic achievement. The paper reviews learning management systems (LMS), video conferencing platforms, interactive content tools, and analytics-based monitoring systems. It also highlights best practices for educators to optimize remote instruction and ensure effective communication, assessment, and feedback.